EVALUASI PEMBINAAN KLUB BOLA VOLI USIA DINI DI KOTA TASIKMALAYA - Septian, Alan (STKIP Pasundan, 2021)
This research was conducted with the aim to evaluate the coaching of athletes at an early age in the sport of volleyball in Tasikmalaya City. This type of research is descriptive method with an evaluation study using the CIPP model, which conducts evaluations on context, input, process, and product components. Subprincipals in the context component include: In the product component, including: 1) Individual program results; 2) Program results as a team. The results of this study show that the evaluation of the achievement of early-age children in Tasikmalaya City in the context component has been well implemented in terms of talent search, athlete coaching and achievement. Judging from the input component of coaching implementation is quite good judging from the condition of athletes and coaches, but in terms of support and funding aspects are still lacking.